The allocation of crop production resources in the southeast of Iran: the application of the water-energy-food nexus approach - Badih Barzin, H.; Hoseini, S. M.; Hashemitabar, M.; Mardani Najafabadi, M. (Frontiers in Environmental Science, 2024)
Due to the expansion of population, economic progress, urbanization, increasing food demands, and diversification of food systems, resources are being excessively exploited and degraded. This is compounded by the challenges posed by climate change and limited resources, as well as inadequate management practices. The concept of water-energy-food (WEF) nexus management recognizes the interdependencies among various resources, such as water, food, and energy, in order to promote sustainable resource management. By establishing a harmonious balance among different objectives, this approach aims to safeguard the well-being of both human societies and the environment, ensuring the fulfillment of needs and the preservation of benefits for both parties.In this study, the water-energy-food (WEF) nexus approach is applied to the Sistan plain, located in the southeastern region of Iran, to effectively redistribute production resources within the agricultural sector. The methodology employed is multi-objective programming, which incorporates various goals. These objectives encompass maximizing farmer revenue and energy derived from food production (measured in calories), while simultaneously minimizing greenhouse gas (GHG) emissions, irrigation water consumption, and overall energy consumption throughout the 2018-2019 crop year. The findings of this study demonstrate that implementing the water-energy-food (WEF) nexus approach in the Sistan plain yields positive outcomes. Despite a reduction in the cultivation area, there is a notable shift towards growing more nutritious crops. This shift not only contributes to food security but also increases crop calorie production from 457.16 million to 565.19 million. Consequently, there is a decrease in irrigation water consumption from 261.62 million to 260.48 million cubic meters, energy consumption from 1400.13 million to 1396.81 million MJ per hectare, and greenhouse gas (GHG) emissions from 0.014 million to 0.0139 million tons per hectare.Analyzing the physical and economic productivity reveals that GHG emissions had the highest productivity in terms of both physical and economic measures in Zahak County. As the WEF nexus approach aims to preserve and prevent environmental degradation, it is recommended to implement development and bio-balance policies utilizing this approach to ensure environmental conservation.